Perception of time-compressed CNC monosyllables by non-native speakers of English - Sood, Sunil Kumar (Journal of All India Institute of Speech and Hearing)
This study reports on the performance of forty young adults on Time-compressed versio of four lists of form B of Northwestern University Auditory Test number 6 recorded in foreign accent. The study aimed at (1) Analyzing the influence of foreign accent on performance of listeners who have not been exposed significantly to it and (2) establishing a pattern of performance of subjects to see if the test can be used in Indian set-up. Time compression levels of 0 and 60% were used at five sensation levels (8, 16, 24, 32 and 40 dB).